The Efforts of A Linen Attendant in Handling Guest Complaints at Chanti Hotel, Semarang - Liemarindu Maharani; Syaiful Ade Septemuryantoro (International Forum of Researchers and Lecturers, 2023)
This study aims to identify and explain the efforts that can be made by linen attendants in handling guest complaints in accordance with the standard operational procedures at the Chanti Semarang Hotel. The data collection methods used in this study are observation, interviews, and documentation so that the data obtained about handling guest complaints will be accurate. The research findings are problems found related to linen that has spots or stains, linen that is damaged or torn, linen that is yellowing. Room attendants are parties who are also responsible and can help maintain linen cleanliness. Efforts that a linen attendant can make to handle guest complaints, whether in terms of efforts to improve deficiencies or efforts to prevent and minimize the occurrence of complaints from guests, so that linens with stain and damage problems can be resolved optimally and can be reused for operations. The conclusion that can be drawn is that if all work is carried out according to standard operational procedures, it will guarantee the smooth operation of the hotel. If problematic linen is optimally resolved, it will have a big impact on the satisfaction of the guests staying, thus reducing the possibility of complaints.